2020
DOI: 10.1002/brb3.1525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toll‐like receptor 4 on depressive‐like behaviors induced by chronic social defeat stress

Abstract: Introduction A growing body of evidence suggests that stress is an important factor in depression, and pro‐inflammatory cytokines contribute to the occurrence and development of depression in both animal models and human patients. Toll‐like receptor 4 (TLR4) has been shown to be a key innate immune pattern recognition receptor involved in the regulation of stress responses and inflammation. However, the exact effects of TLR4 on depressive‐like behaviors induced by chronic social defeat stress (CSDS) are not kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…This conclusion is strongly supported by the previous studies that showed that knockout of Cnr2 in the brain could attenuate psychomotor, depression- and anxiety-like behaviors in mice ( Liu Q.R. et al, 2017 ) and that blocking Tlr4 could reduce the anxiety- and depression-like behaviors ( Strekalova et al, 2015 ; Zhang et al, 2020 ). In addition, we also found that the other two neuroinflammation-related genes Fgf2 and Cbln1 were differentially expressed in the hippocampus of aging mice, both of which have been demonstrated to affect fear conditioning and spatial memory processes in aged animals ( Hirai et al, 2005 ).…”
Section: Discussionsupporting
confidence: 70%
“…This conclusion is strongly supported by the previous studies that showed that knockout of Cnr2 in the brain could attenuate psychomotor, depression- and anxiety-like behaviors in mice ( Liu Q.R. et al, 2017 ) and that blocking Tlr4 could reduce the anxiety- and depression-like behaviors ( Strekalova et al, 2015 ; Zhang et al, 2020 ). In addition, we also found that the other two neuroinflammation-related genes Fgf2 and Cbln1 were differentially expressed in the hippocampus of aging mice, both of which have been demonstrated to affect fear conditioning and spatial memory processes in aged animals ( Hirai et al, 2005 ).…”
Section: Discussionsupporting
confidence: 70%
“…Another potential mechanism of action is the anti-inflammatory effect of HDAC6 inhibition 23 . Inflammation has been correlated with depression in a number of studies 35 38 , therefore, alleviating inflammatory signaling may be a mode of action of Hdac6 depletion. We have shown specifically in CF mouse models that depletion of Hdac6 results in reduced inflammation and better clearance of bacteria in airways from infected mice 23 .…”
Section: Discussionmentioning
confidence: 99%
“…And a certain number of studies also revealed both chronic stress and LPS challenges induced distinct molecular and behavioral changes in mice ( Espinosa-Oliva et al, 2011 ; Couch et al, 2016 ). For instance, Toll-like receptors (TLRs) play an important role in this depressive behavioral changes ( Habib et al, 2015 ; Zhang.W., et al, 2020 ). Further studies are needed to address whether antidepressant effects of SLDS also affects TLRs pathway.…”
Section: Discussionmentioning
confidence: 99%
“…OFT was conducted the day after FST as described ( Sevastre-Berghian et al, 2020 ). OFT has been reported as a scientifically valid method to evaluate the general locomotivity and anxiety levels in animal experiments ( Sevastre-Berghian et al, 2020 ; Zhang et al, 2020 ). Briefly, the open field (Techman software, China) 36 cm × 36 cm was surrounded by walls.…”
Section: Methodsmentioning
confidence: 99%